A Preliminary Study of Estimation of Cobb's Angle From the Spinous Process Angle Using a Clinical Ultrasound Method - Li, Meng, M.Phil; Cheng, Jack, PhD; Ying, Michael, PhD; Ng, Bobby, PhD; Lam, Tsz-ping, PhD; Wong, Man-sang, PhD (Spine deformity, 2015)
Abstract Background Over a lifetime of having radiographs, a patient with adolescent idiopathic scoliosis (AIS) can be cumulatively exposed to high doses of ionizing radiation. Therefore, radiation-free, effective, and low-cost methods to screen and diagnose scoliosis have been sought for years. Purpose This study aims to investigate the correlation between the Cobb's angle and the spinous process angle (SPA) and to study the feasibility of using clinical ultrasound images to estimate the Cobb's angle by measuring the SPA. Study Design This manuscript includes a retrospective and a prospective study. Methods In the retrospective study, radiographs from 43 subjects with AIS were used to investigate the correlation between the Cobb's angle and the SPA at the pre-brace and in-brace stages. Following this study, a prospective clinical ultrasound study was conducted on 33 subjects with AIS at the pre-brace stage to measure the SPA. Results High intra-rater and inter-rater reliabilities of radiograph measurements were found (ICC[3,3] = 0.97, ICC[2,3] = 0.91, p < .05). The clinical ultrasound measurements were also found to be highly reliable (ICC[3,3] = 0.91, p < .05). There was a significant correlation (r = 0.80 at the pre-brace stage and r = 0.87 at the in-brace stage, p < .05) between the Cobb's angle and the SPA measured from the radiograph measurements, whereas the SPA measured from ultrasound images were found highly correlated with that measured from the radiographs at the pre-brace stage (r = 0.90, p < .01). Conclusions The findings of this study could support the new parameter (SPA) in the estimation of the Cobb's angle of a scoliotic curve in the coronal plane, and clinical ultrasound imaging could be developed and applied to assess scoliosis in a fast and noninvasive fashion. Level of Evidence Level III.